Find the information you're looking for at Westonci.ca, the trusted Q&A platform with a community of knowledgeable experts. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.
Sagot :
Alright, let’s work through the solution step-by-step:
The problem at hand is to solve the equation [tex]\(4(18 - 3k) = 9(k + 1)\)[/tex].
1. Distribute the constants on both sides:
- Start by distributing the 4 on the left side:
[tex]\[ 4(18 - 3k) = 4 \cdot 18 - 4 \cdot 3k = 72 - 12k \][/tex]
- Next, distribute the 9 on the right side:
[tex]\[ 9(k + 1) = 9k + 9 \][/tex]
2. Set the left side equal to the right side:
[tex]\[ 72 - 12k = 9k + 9 \][/tex]
3. Combine like terms:
- To isolate the variable [tex]\(k\)[/tex], we move all [tex]\(k\)[/tex]-terms to one side and constants to the other:
[tex]\[ 72 - 9 = 9k + 12k \][/tex]
- Simplify the equation:
[tex]\[ 63 = 21k \][/tex]
4. Solve for [tex]\(k\)[/tex]:
- Divide both sides by 21 to get [tex]\(k\)[/tex]:
[tex]\[ k = \frac{63}{21} \][/tex]
- Simplify the fraction:
[tex]\[ k = 3 \][/tex]
Therefore, the solution to the equation [tex]\(4(18 - 3k) = 9(k + 1)\)[/tex] is [tex]\(k = 3\)[/tex].
The problem at hand is to solve the equation [tex]\(4(18 - 3k) = 9(k + 1)\)[/tex].
1. Distribute the constants on both sides:
- Start by distributing the 4 on the left side:
[tex]\[ 4(18 - 3k) = 4 \cdot 18 - 4 \cdot 3k = 72 - 12k \][/tex]
- Next, distribute the 9 on the right side:
[tex]\[ 9(k + 1) = 9k + 9 \][/tex]
2. Set the left side equal to the right side:
[tex]\[ 72 - 12k = 9k + 9 \][/tex]
3. Combine like terms:
- To isolate the variable [tex]\(k\)[/tex], we move all [tex]\(k\)[/tex]-terms to one side and constants to the other:
[tex]\[ 72 - 9 = 9k + 12k \][/tex]
- Simplify the equation:
[tex]\[ 63 = 21k \][/tex]
4. Solve for [tex]\(k\)[/tex]:
- Divide both sides by 21 to get [tex]\(k\)[/tex]:
[tex]\[ k = \frac{63}{21} \][/tex]
- Simplify the fraction:
[tex]\[ k = 3 \][/tex]
Therefore, the solution to the equation [tex]\(4(18 - 3k) = 9(k + 1)\)[/tex] is [tex]\(k = 3\)[/tex].
We appreciate your visit. Hopefully, the answers you found were beneficial. Don't hesitate to come back for more information. Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. Thank you for using Westonci.ca. Come back for more in-depth answers to all your queries.